Perkembangan Literasi Digital Pendidikan Kewarganegaraan Dalam Lingkungan Perguruan Tingggi - Shyntia Suci Ramadhan; Rakha Satya Maldini; Radhya Putri Salwa Alifah (JURNAL PENCAKAR (Pendidikan Pancasila dan Kewarganegaraan), 2026)
This article is about the9importance of digital literacy for strengthening civic education. Citizenship education is an integral part and is reflected in9courses and forms of learning at the higher education level. To achieve the goals of civics education, various functions and roles of civics education are then planned and implemented in tertiary institutions as a form of increasing student knowledge. Citizenship is very important in the current era of globalization. We need to manage and balance the skills of artificial intelligence and social intelligence to help solve problems. The world of education is an example of how data can be used, namely to move and connect everything, including literacy. Literacy itself is a person's9ability to process and understand information when carrying out the process of reading and writing. In its development, the definition of literacy always evolves according to the challenges of the times, in this era of globalization everything is completely digital, an example that we can see is the digital library, from here we can read anywhere and anytime. In short, with It equips students with the skills needed in today's increasingly technological era, including leadership, digital literacy, communication, emotional intelligence, and global citizenship. The challenge of citizenship education is to provide knowledge as well as critical.